The mechanism of defect induced hydroxylation on pyrite surfaces and implications for hydroxyl radical generation in prebiotic chemistry. (1st January 2019) - Xian, Haiyang; Zhu, Jianxi; Tan, Wei; Tang, Hongmei; Liu, Peng; Zhu, Runliang; Liang, Xiaoliang; Wei, Jingming; He, Hongping; Teng, H. Henry
Abstract: The generation of reactive oxygen species H2 O2 and OH from pyrite in anaerobic environments plays an important role in the evolution of early Earth. What remains debatable is the underlying mechanism leading to the OH generation reactions. Using a comprehensive approach combining X-ray photoelectron spectroscopy and ab initio calculations, we investigated binding energies and valence band structures of defective pyrite surfaces in an attempt to interrogate pyrite-mediated H2 O dissociation in the presence and absence of crystal defects. The results show that, while energetically inhibited on perfect crystal faces, H2 O dissociation is thermodynamically favored at defective sites. Furthermore, the formation of surface defects can lead to an energy shift in valence bands and thereby forming two defect states. Simultaneously, interaction between both defect states and water molecules makes the hydroxylation energetically favored on the pyrite surface. The hydroxylation occurs through proton transfer from water to a defective S monomer, resulting in an FeO(H)···HS structure. These findings provide new insight into pyrite-assisted OH formation processes in anaerobic conditions and may be important for understanding prebiotic chemistry and the evolution of early Earth.